2005
DOI: 10.1161/01.str.0000183617.54752.69
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Gene Polymorphism and Ischemic Stroke

Abstract: Background and Purpose-The tissue-type plasminogen activator (tPA) Ϫ7351CϾT and the plasminogen activator inhibitor type 1 (PAI-1) -675 4G Ͼ5G polymorphisms influence transcriptional activity. Both variants have been associated with myocardial infarction, with increased risk for the T and 4G allele, respectively. In this study we investigated the possible association between these polymorphisms, the respective plasma protein levels, and ischemic stroke. Methods-In the Sahlgrenska Academy Study on Ischemic Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 35 publications
2
60
1
2
Order By: Relevance
“…Several studies have investigated the regulating role of t-PA in the degradation of the thrombus and founded that the protein appears to activate the transformation of plasminogen to plasmin, which digests the fibrin clot [14,15]. The I/D polymorphism in the gene coding for t-PA was associated with an increased or decreased levels in serum t-PA. Further, the homozygous genotype I/I of the t-PA gene was associated with a higher risk of MI [16]. In this study, we found no significant differences between the two groups in terms of allelic and genotypic frequencies.…”
Section: Discussioncontrasting
confidence: 51%
“…Several studies have investigated the regulating role of t-PA in the degradation of the thrombus and founded that the protein appears to activate the transformation of plasminogen to plasmin, which digests the fibrin clot [14,15]. The I/D polymorphism in the gene coding for t-PA was associated with an increased or decreased levels in serum t-PA. Further, the homozygous genotype I/I of the t-PA gene was associated with a higher risk of MI [16]. In this study, we found no significant differences between the two groups in terms of allelic and genotypic frequencies.…”
Section: Discussioncontrasting
confidence: 51%
“…The intra-and inter-assay coefficients of variation were 5.3% and 13.3%, respectively. The serum levels of high-sensitivity C-reactive protein (hsCRP) were analyzed in a solid-phase chemiluminescent immunometric assay, the plasma levels of tissue type plasminogen activator (t-PA) antigen were analyzed by ELISA and plasma fibrinogen was measured with an automated clot rate assay, as described previously [20][21][22].…”
Section: Blood Sampling and Vwf Measurementmentioning
confidence: 99%
“…The number of individuals for whom the values for risk factors and other covariates were missing, have been reported previously [19][20][21][22]. In the logistic regression, missing values were replaced by dummy variables for the covariates being categorical variables.…”
Section: Missing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Their results show that t-PA -7351 C>T and PAI-1 -675 4G>5G polymorphism affects transcriptional activity and that these two variants are connected to myocardial infarction with an increased risk in the case of T and 5G alleles. However, in the case of cerebral ischemia this connection does not occur, so it assumed that the role of t-PA and PAI-1 is more complex in brain than in heart (30). Contrary to these, other studies consider the plasminogen activator system to be the one which plays the key role in the pathogenesis of cerebral ischemia (31).…”
Section: Discussionmentioning
confidence: 99%